Rola Towarzystwa Budownictwa Społecznego w zaspokajaniu lokalnych potrzeb mieszkaniowych - Biniasz-Celka, Danuta (Studia Prawa Publicznego, 2020)
By the Act of 8 March 1990 on Municipal Self-Government, the legislator imposed a wide range of tasks to be performed by the municipality, including meeting the community’s needs in the area of municipal housing. The aim of the study is to present a legal entity that is autonomous from the commune and managed as a limited liability company, namely the Towarzystwo Budownictwa Społecznego (TBS) [Social Housing Society]. It operates under the Commercial Companies Code of 15 September 2000 within the scope resulting from Article 27(1) and (2) of the Act of 26 October 1995 on Certain Forms of Housing Promotion, thus performing the municipality’s housing tasks. TBS companies have been equipped with a legal personality primarily to become a more effective guarantor of the proper implementation of public tasks. The availability and standard of housing play a key role in meeting the housing needs of households. For those social groups that are unable to finance the purchase of a dwelling at market prices on their own, rental housing is a beneficial solution to meet their housing needs. The operations of the TBS are not subject to the principles of the market economy. The specificity of the company’s activity is that the primary and principal statutory objective cannot be profit-making, i.e. to seek to generate and maximise profits, but that any income must be allocated to statutory objectives. However, nothing stands in the way of such companies performing secondary and accessory activities at the same time, the income from which will support their non-commercial statutory objectives.